Isolated petrous apex ectopic craniopharyngioma (Medical Journal of Indonesia, 2015)
Primary ectopic craniopharyngioma is a rare entity. Isolated petrous apex bone location has not been reported previously. This study reports a case of 26-year-old male with right abducent nerve palsy. CT and MRI imaging reveal right petrous apex cystic lesion. No sellar or suprasellar region involvement was found. Endoscopic endonasal transphenoid approach has been successfully performed. Histopathology examination confirms the diagnosis of adamantinomatous craniopharyngioma. So far, itâs probably the first case report of primary ectopic craniopharyngioma isolated in the petrous apex. This case report supports the premise that primary ectopic craniopharyngioma is a multifactorial process that starts with an error from migrated embryological cells.